Search for the Higgs boson in the H→WW→ℓνjj decay channel at √s=7 TeV with the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Abdel Khalek, S; Abdelalim, A; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; et al. (2012)
A search for the Standard Model Higgs boson has been performed in the H→WW→ℓνjj channel using 4.7 fb-1 of pp collision data recorded at a centre-of-mass energy of s=7 TeV with the ATLAS detector at the Large Hadron Collider. Higgs boson candidates produced in association with zero, one or two jets are included in the analysis to maximize the acceptance for both gluon fusion and weak boson fusion Higgs boson production processes. No significant excess of events is observed over the expected background and limits on the Higgs boson production cross section are derived for a Higgs boson mass in the range 300 GeV